Enforcing order: Territorial reach and maritime piracy. (July 2017) - Daxecker, Ursula; Prins, Brandon C.
Existing studies of piracy focus attention on the institutional determinants of maritime piracy, but neglect variation in governments' reach over territory. We argue that the effect of state capacity on piracy is a function of states' ability to extend authority over the country's entire territory. We expect that government reach—a function of geographic factors such as the distance between a country's capital and its coastline—mediates the effect of state capacity on piracy. Weak governments allow for the planning and implementation of attacks and reduce the risk of capture, but particularly so if sufficient distance separates pirates from political authority. An empirical analysis of country-year data on maritime piracy collected by the International Maritime Bureau for the 1995–2013 period shows that capital–coastline distance mediates the effect of institutional fragility on piracy as hypothesized. These results remain robust for alternative operationalizations of state capacity and reach. In addition, the models perform well in terms of predictive power, forecasting piracy quite accurately for 2013. The expectations and evidence presented in this paper help explain why states with intermediate levels of state capacity but low levels of reach—such as Indonesia, Tanzania or Venezuela—struggle with substantial incidence of piracy.